Apoptosis Induction, a Sharp Edge of Berberine to Exert Anti-Cancer Effects, Focus on Breast, Lung, and Liver Cancer - Zhu, Yi; Xie, Na; Chai, Yilu; Nie, Yisen; Liu, Ke; Liu, Yufei; Yang, Yang; Su, Jinsong; Zhang, Chuantao (Frontiers in Pharmacology, 2022)
Cancer is predicted to be the leading cause of death and the single most important barrier to increase life expectancy in every country of the world in the 21st century. It is urgent to find effective drugs from natural compounds to treat cancers. As a well-known isoquinoline alkaloid, berberine (BBR) exerts potential proapoptotic effect on multiple cancers drawing world-wide attention. Studies have proved that BBR has good therapeutic effects on three cancers (breast, lung, and liver cancer) via the inhibition of the cell proliferation, metastasis and invasiveness through the promotion of apoptosis. The involved mechanisms were related to the regulation of AMPK, MAPK, and AKT pathways. In this review, we provide a timely and comprehensive summary of the ADMET process and the detailed molecular mechanisms of BBR on the above three cancers. Meanwhile, we discussed the existing challenges and provided valuable information for the comprehension of BBR in the treatment of cancers.